(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To compare the percentage of slip difference using the standing and supine lateral radiographs in symptomatic degenerative lumbar Spondylolisthesis. Methods: This descriptive study was conducted in department of Spine surgery unit Hayat Abad Medical Complex Peshawar from 2nd January 2019 to 2nd December 2020.All adults patients of both gender with low backache due to degenerative Spondylolesthesis meeting the inclusion criteria were enrolled in this study. All patients underwent standing and supine lateral radiographs. Slip of Spondylolesthesis was calculated according to Dupuis technique. Percentage of slip on standing radiographs were compared with supine and p value calculated using student t test. P value <0.05 was considered significant. Results: The total number of patients were 30. The mean age was 44.60±6.62 years. Male patients were 5 (16.7%) and female 25 (83.3%). Spondylolesthesis was noted at L4-L5 level in 17 (56.66%) patients while 13 (43.33%) patients had L5-S1 level involved. The mean slip percentage on standing x ray was 34.60± 20.03 and on supine 11.97±8.65 showing a significant slip reduction on supine radiographs.(p=0.01) Conclusion: Supine lateral radiographs showed significant slip reduction in degenerative Spondylolesthesis. We therefore recommend routine use of supine lateral radiographs for the assessment of degenerative Spondylolesthesis.